Iran - Medium Term Framework for Transition : Converting Oil Wealth to Development - World Bank (Washington, DC, 2013)
Iran is about 10 percent of Gross Domestic Product (GDP) off an economic equilibrium that will reduce unemployment and improve significantly people's welfare by converting oil wealth into sustainable development. 1) It is about 10 percent of GDP short in the additional savings and investment needed to attain growth that will reduce unemployment. 2) Optimal management of Iran's oil to provide the above needed savings and achieve an optimal balance between consumption and savings that will sustain the benefits from oil after it is exhausted, requires that it allocate about 10 percent of GDP more for savings and investment and less to consumption from its oil wealth. 3) That 10 percent adjustment can come from the reform of Iran's inefficient energy subsidy system, which also happens to average about 10 percent of the GDP a year. These expenditures can be transformed into budget surpluses that will provide ample credit to the private sector to grow. This adjustment -at the core of Iran's medium and long term fiscal strategy- is a main pillar of Iran's transition to a market economy led by the private sector. Hence, the critical importance of alternative management strategy of oil wealth in providing the needed additional savings to enable private sector financing and promote the transition to a private sector led economy.